Implicating the effects of consuming water with a high level of arsenic content: highlighting the cause and consequences of arsenic contamination in drinking water - Sumant Kumar Verma; ShriRam Chaurasia (Water Practice and Technology, 2024)
Contamination of groundwater due to arsenic (As) and problems faced by drinking the contaminated water have been identified worldwide. The integration of biogeochemical processes has led to the dissolution of naturally occurring As into the groundwater. The goal of this investigation is mainly to determine the presence of As in drinking water and consequences faced by human beings by drinking such contaminated water. Scope of this issue has not yet undergone a full epidemiological examination in any Indian region. However, in India, little is known about the disease caused by arsenicosis. Therefore, the present study discusses various natural and anthropogenic sources of As in groundwater involving its speciation and mobilization pattern in groundwater. Appropriate review on the issues of As contamination in groundwater has been conducted in various regions across the globe followed by the epidemiology and toxicity mechanisms of As in human beings. Various remediation techniques have been adopted for mitigating the major impact of As contamination depending upon the conventional, modern, and hybrid technologies for removing the As from several regions of India. HIGHLIGHTS A detailed discussion has been done on global groundwater contamination through various sources with ranges, the mechanism of arsenic contamination within the groundwater system, the sources, speciation, and mobility of arsenic.; A detailed discussion has been done on health risks caused by the consuming water contaminated with arsenic.; Effective techniques for the removal are studied.;